Pengaruh Metode Pembelajaran Mind Mapping Terhadap Minat Belajar IPA Peserta Didik Kelas Tinggi di SDN 284 Labuaja Kecamatan Kahu Kabupaten Bone - Abd Hafid; Muhammad Amran; A. Nurul Azizah Purnama Muhlis (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This research is a type of quantitative research with the type of ex post facto research. This study aims to determine the effect of the Mind Mapping learning method on the interest in learning science of high-class students at SDN 284 Labuaja, Kahu District, Bone Regency. The results of the descriptive analysis research obtained that the mind mapping learning method had an average of 68.14 and a percentage of 76% in the good category and students' interest in learning science with an average of 65.28 and a percentage of 56% in the good category. The results of this study indicate that there is a significant effect on the application of the Mind mapping learning method on the interest in learning science for class VI students at SDN 284 Labuaja, Kahu District, Bone Regency. This is indicated by the analysis of hypothesis testing with T test, obtained tcount of 5.770 and ttable with 5% significance of 2.00958 so that tcount > ttable.